Efek Antifilaria Ekstrak Etanolik Akar Calotropis gigantea (WiIld) Dryand ex.Ait. f terhadap Brugia Malayi pada Gerbil (Meriones unguiculatus): Antifilarial Effect of Ethanolic Extract of Calotropis gigantea - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Lymphatic filariasis is still important public health problem in Indonesia. Recently the drug of choice for this disease is diethylcarbamazine (DEC), but administrating this medicine shows side effects and make it is hardly accepted in the community. This study was aimed to investigate the effect of ethanolic extract of Calotropis gigantea (Willd) Dryand ex. Ait . f on microfilaria and macrofilaria Brugia malayi as an effort to look for new alternative treatment for malayi filariasis. This Calotropis gigantea plants in India is used as anthelmintic and elephantiasis drugs. Jirds were divided into 7 groups: ethanolic extract group, petroleum eter fraction, ethyl acetate fraction, ethanol fraction, and water fraction group, each was given the remedy 640mg/kgBW, the positive control were given DEC 250mg/kgBW and negative control. The density of microfilaria reached up to 15/20111. The remedy was given for 12 days, orally. The observation of microfilaricidal effect was done three times to reduction of microfilaria density after treatment. The observation of macrofilaricidal effect was the capability of macrofilaria in vitro culture media everyday for 15 days. The result showed that ethanolic extract and its fraction could reduced microfilaremia density, ethanolic extract 3,13%